2018
DOI: 10.1159/000489829
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Extracellular Traps in the Second Decade

Abstract: Nearly 15 years after the first description of neutrophil extracellular traps (NETs), our knowledge concerning this structure has expanded considerably. Initially, NETs were considered solely an elaborate function of the innate immune system to combat invading microorganisms. Successively it became clear that NETs have farther-reaching capabilities. They are involved in a series of pathophysiological mechanisms ranging from inflammation to thrombosis where they fulfill essential functions when produced at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
231
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(245 citation statements)
references
References 75 publications
(83 reference statements)
2
231
1
11
Order By: Relevance
“…Neutrophils are the first line of defense against pathogens. Besides phagocytosis and degranulation, a third strategy to combat microbes is the formation of NETs . Very soon after the discovery of NETs and using a mouse model of sepsis, it was shown that platelets are required to fuel the formation of NETs.…”
Section: Role Of Platelet Tlr4 In the Immune Responsementioning
confidence: 99%
See 3 more Smart Citations
“…Neutrophils are the first line of defense against pathogens. Besides phagocytosis and degranulation, a third strategy to combat microbes is the formation of NETs . Very soon after the discovery of NETs and using a mouse model of sepsis, it was shown that platelets are required to fuel the formation of NETs.…”
Section: Role Of Platelet Tlr4 In the Immune Responsementioning
confidence: 99%
“…If these reactions occur systemically and are sustained for a long period, as observed in sepsis, they can lead to DIC followed by multiorgan failure and even death. In addition, under sustained sterile inflammatory conditions, they can be involved in the pathogenesis of both arterial or venous thrombotic diseases as well as autoimmune‐related disorders such as lupus, arthritis, or vasculitis …”
Section: Role Of Platelet Tlr4 In the Immune Responsementioning
confidence: 99%
See 2 more Smart Citations
“…New insights have been gained into the mechanisms of neutrophil apoptosis and the potential anti- inflammatory consequences of promoting accelerated apoptosis. Furthermore, non-apoptotic forms of neutrophil cell death have been identified that may lead to pro-inflammatory consequences in both infective and autoimmune diseases [32]. …”
Section: New Ways To Die – Neutrophil Cell Deathmentioning
confidence: 99%